2020
DOI: 10.1186/s12891-020-03732-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole body vibration with exercise therapy versus exercise therapy alone on flexibility, vertical jump height, agility and pain in athletes with patellofemoral pain: a randomized clinical trial

Abstract: Background Patellofemoral pain (PFP) is the most prevalent orthopedic problem in active young adults. Due to its multifactorial etiology, a variety of therapeutic measures have been adopted to treat PFP, including exercise therapy, electrotherapy, and manual therapy. It has also been suggested that whole body vibration (WBV) can improve neuromuscular function in persons with knee problems. The aim of the present study was to evaluate the effects of adding WBV to routine exercise programs on fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Similarly, Rogan et al concluded that adding WBV to physical therapy did not improve muscle strength in healthy elderly people [ 95 ], and Anwer and colleagues found no beneficial effects of WBV on quadriceps muscle strength in patients with knee osteoarthritis [ 96 ]. More recently, Rasti and colleagues conducted a randomized clinical trial to compare the effects of physical training with and without WBV on flexibility, vertical jump height, agility, and pain in 24 athletes with patellofemoral pain (PFP), a well-known musculoskeletal condition prevalent among active young adults [ 97 ]. Interestingly, physical therapy with and without WBV was observed to significantly reduce pain and increase agility, vertical jump height and flexibility in athletes with PFP.…”
Section: Wbv Vs Exercise: Do We Have a Chance?mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Rogan et al concluded that adding WBV to physical therapy did not improve muscle strength in healthy elderly people [ 95 ], and Anwer and colleagues found no beneficial effects of WBV on quadriceps muscle strength in patients with knee osteoarthritis [ 96 ]. More recently, Rasti and colleagues conducted a randomized clinical trial to compare the effects of physical training with and without WBV on flexibility, vertical jump height, agility, and pain in 24 athletes with patellofemoral pain (PFP), a well-known musculoskeletal condition prevalent among active young adults [ 97 ]. Interestingly, physical therapy with and without WBV was observed to significantly reduce pain and increase agility, vertical jump height and flexibility in athletes with PFP.…”
Section: Wbv Vs Exercise: Do We Have a Chance?mentioning
confidence: 99%
“…Interestingly, physical therapy with and without WBV was observed to significantly reduce pain and increase agility, vertical jump height and flexibility in athletes with PFP. However, WBV implementation to routine physical therapy increased the latter’s effects on flexibility, confirming vibratory training as a valuable additional strategy to increase the effectiveness of conventional physical therapy and optimize athletic performance [ 97 ]. In agreement with this, Gloeckl et al demonstrated that balance training performed on a WBV platform induced greater benefits in terms of balance performance and muscle power than conventional training in patients with severe chronic obstructive pulmonary disease (COPD) and functional impairment [ 98 ].…”
Section: Wbv Vs Exercise: Do We Have a Chance?mentioning
confidence: 99%
“…All 5 studies focused on pain intensity, 4 [ 13 , 14 , 16 , 17 ] of them reported VAS score and the 1 [ 15 ] other reported NPRS score. After converting NPRS value to VAS, data from 5 articles were pooled together.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects of this study are swimmers. 1 This article takes a more in-depth look at how the lower body joints are trained. This lays the groundwork for further exploration of the best options for strength training.…”
Section: Introductionmentioning
confidence: 99%